Toward estimating the plasmaspheric plasma density by using both the field-line resonance and the TEC - 河野, 英昭; 才田, 聡子; 上野, 玄太; 樋口, 知之; 中野, 慎也; 湯元, 清文; Hideaki, Kawano; Satoko, Saita; Genta, Ueno; Tomoyuki, Higuchi; Shin'ya, Nakano; Kiyohumi, Yumoto (2010)
第34回極域宙空圏シンポジウム 12月3日（金） 国立極地研究所 2階大会議室 conference object